1993
DOI: 10.1099/00221287-139-12-3139
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and biosynthesis of indole antibiotics produced by Xenorhabdus nematophilus

Abstract: ~We have investigated the mechanism of action and physiology of production of the indole derivative antibiotics produced by the nematode-associated, entomopathogenic bacterium Xenorhabdus nernatophilus. Maximum antibiotic concentration was reached during the late stationary phase of growth, and the antibiotic yield was appreciably enhanced by supplementation with tryptophan. Antibiotic biosynthesis apparently involved the removal of the side-chain carboxyl (C-1) carbon of tryptophan. The C-3 methylene carbon o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 18 publications
(28 reference statements)
1
49
0
Order By: Relevance
“…nematophila produces antibacterial peptides to control the growth of other bacterial strains associated with the larval prey (1,26,43,45). These antibiotics serve two critical functions: (i) they prevent putrefaction of the larval carcass by eliminating competing bacterial strains, and (ii) they provide the host strain unrestricted access to the available nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…nematophila produces antibacterial peptides to control the growth of other bacterial strains associated with the larval prey (1,26,43,45). These antibiotics serve two critical functions: (i) they prevent putrefaction of the larval carcass by eliminating competing bacterial strains, and (ii) they provide the host strain unrestricted access to the available nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…ANV2 did not produce antibiotics, crystal proteins, or OpnB (Table 2). These products have been previously shown to be induced during the post-exponential-growth phase (23,24,25,42). ANV2 also possessed dramatically reduced levels of fimbriae, was unable to stimulate hemagglutination, lacked hemolytic activity, and did not swarm on agar plates.…”
Section: Resultsmentioning
confidence: 99%
“…However, the biochemical properties of these products are very different. The antibiotics produced by Xenorhabdus are either indole derivatives or belong to the xenocoumacin or xenorhabdin family of compounds, while the antibiotics of Photorhabdus are hydroxystilbenes (2,24,42). The biochemical properties of the crystal proteins of the respective bacteria are also very different (7,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paramomycin, indole, ethyl iso-allocholate and phenol have been reported to possess strong antimicrobial properties (Sundar and Chang, 1993;Meyer et al, 1999;Huang et al, 2011). Paramomycin which was originally isolated from the fermentation of Streptomyces in 1956 (Lu et al, 1997) has been reported to possess broad spectrum activity against Gram-negative and Gram-positive bacteria (Stead, 2000) such as E. coli, S. aureus, S. pyogenes, P. vulgaris and K. Pneumoniae (Francois et al, 2004) as well as some protozoa and cestodes (Davidson et al, 2009).…”
Section: Determination Of Mechanisms Of Antibiosis (Bactericidal or Bmentioning
confidence: 99%